Novel microwell-based spectrofluorimetric method assisted with fluorescence plate reader for determination of ruxolitinib: Optimization by response surface methodology and application to in-vitro drug release, content uniformity testing and analysis of u… - Abdullah M. Al-Hossaini; Abdullah S. Al-Mutairi; Ibrahim A. Darwish; Ahmed H. Bacheit; Awadh M Ali; Hany W. Darwish (Talanta Open, 2023)
ABSTRACT: This study describes, for the first time, the development and validation of a novel microwell-based spectrofluorimetric method assisted with fluorescence plate reader (MWP-SFL) for determination of ruxolitinib (RUX), a drug approved for the treatment of moderate or high-risk myelofibrosis and polycythemiavera, in tablets and urine. The proposed MWP-SFL method was performed in 96-microwell plate and involved the direct measurement of the native fluorescence of RUX by a fluorescence plate reader in aqueous medium at 405 nm after its excitation at 310 nm. The response surface methodology (RSM) was used to establish the optimum procedures and conditions of the analysis. The fluorescence signal was linearly correlated with the RUX concentrations in the range of 0.8 – 250 ng mL−1. The MWP-SFL method limits of detection (LOD) and quantitation (LOQ) were 2.89 and 8.75 ng mL−1, respectively. The accuracy and precision of the method were confirmed as the recovery was 99.66 – 102.29% with relative standard deviation (RSD) values of 0.47 – 1.37%. The MWP-SFL method was successfully applied to the determination of RUX in its pharmaceutical tablets, tablets dissolution testing, tablets content uniformity and urine samples with good precision and accuracy. The proposed MWP-SFL method combined the benefits of the intrinsically high sensitivity of the spectrofluorimetric measurement and the high throughput analytical property of the microwell-based approach. The MWP-SFL method also stands out for its straightforward procedures and use of water as a solvent and little amounts of sample solutions, both of which are consistent with its green chemistry philosophy. These advantages gave the proposed MWP-SFL a high potential value for determination of RUX in quality control and clinical laboratories.